Behaviour of grouted pipe splice under incremental tensile load - Ling, Jen Hua (2012)
This paper presents the behaviour and performance of grouted splice connection. A sleeve is utilized to confine the splicing of two discontinued bars, and as a result, the bond performance between the bars and the bonding material can be improved. Two new sleeves, fabricated from standard size steel pipes, were proposed and the grouted splice specimens were tested under incremental tensile load until failure of the specimens, either by bar bond-slip or bar fracture failure. The behaviour of the specimens, which is represented by the load–displacement response, is discussed, and it is found that the geometrical configurations of the sleeve provide significant influence to the bond performance due to the effects of confinement generated by the sleeve.